Exacerbations among chronic bronchitis patients treated with maintenance medications from a US managed care population: an administrative claims data analysis - AbuDagga, Azza (Dove Medical Press, 2013)
PURPOSE: Chronic obstructive pulmonary disease (COPD) exacerbations are the leading cause of hospital admission and death among chronic bronchitis (CB) patients. This study estimated annual COPD exacerbation rates, related costs, and their predictors among patients treated for CB. METHODS: This was a retrospective study using claims data from the HealthCore Integrated Research Database (HIRD(SM)). The study sample included CB patients aged ≥ 40 years with at least one inpatient hospitalization or emergency department visit or at least two office visits with CB diagnosis from January 1, 2004 to May 31, 2011, at least two pharmacy fills for COPD medications during the follow-up year, and ≥2 years of continuous enrollment. COPD exacerbations were categorized as severe or moderate. Annual rates, costs, and predictors of exacerbations during follow-up were assessed. RESULTS: A total of 17,382 individuals treated for CB met the selection criteria (50.6% female; mean ± standard deviation age 66.7 ± 11.4 years). During the follow-up year, the mean ± standard deviation number of COPD maintenance medication fills was 7.6 ± 6.3; 42.6% had at least one exacerbation and 69.5% of patients with two or more exacerbations during the 1 year prior to the index date (baseline period) had any exacerbation during the follow-up year. The mean ± standard deviation cost per any exacerbation was $269 ± $748 for moderate and $18,120 ± $31,592 for severe exacerbation. The number of baseline exacerbations was a significant predictor of the number of exacerbations and exacerbation costs during follow-up. CONCLUSION: Exacerbation rates remained high among CB patients despite treatment with COPD maintenance medications. New treatment strategies, designed to reduce COPD exacerbations and associated costs, should focus on patients with high prior-year exacerbations.